2021
DOI: 10.3390/su13041657
|View full text |Cite
|
Sign up to set email alerts
|

Science-Based Targets: On Target?

Abstract: Companies are increasingly seeking to align their actions with the goals of the Paris Agreement. Over 1000 such companies have committed to the science-based targets initiative which seeks to align corporate carbon reduction targets with global decarbonisation trajectories. These ‘science-based targets’ are developed using a common set of resources and target-setting methodologies, then independently assessed and approved by a technical advisory group. Despite the initiative’s rapid rise to public prominence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 19 publications
(24 reference statements)
2
45
0
1
Order By: Relevance
“…This indicates that academia is just beginning to study SBTs and data for empirical analysis is just beginning to emerge. The studies employ a variety of methods, such as statistical analyses informed by theories of corporate climate behavior (e.g., [ 52 , 53 , 57 ]), case studies of selected companies (e.g., [ 50 , 51 ]), and reviews of SBT methods or SBTi guidelines (e.g., [ 26 , 44 , 49 ]), with many studies employing a mix of methods. Some studies focus on companies in specific regions (Europe, Asia, the UK, and Japan [ 50 , 51 , 56 , 58 ]), or sectors (construction [ 47 ]), while most have a global scope.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicates that academia is just beginning to study SBTs and data for empirical analysis is just beginning to emerge. The studies employ a variety of methods, such as statistical analyses informed by theories of corporate climate behavior (e.g., [ 52 , 53 , 57 ]), case studies of selected companies (e.g., [ 50 , 51 ]), and reviews of SBT methods or SBTi guidelines (e.g., [ 26 , 44 , 49 ]), with many studies employing a mix of methods. Some studies focus on companies in specific regions (Europe, Asia, the UK, and Japan [ 50 , 51 , 56 , 58 ]), or sectors (construction [ 47 ]), while most have a global scope.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless, the correlation of SBT adoption and CDP scores provides additional (albeit limited) support for increased credibility as a motivator for SBT adoption. Giesekam et al [ 57 ] also observed that a significant proportion of global companies setting SBTs had already earned a high CDP score, reinforcing the importance of past success in driving SBT adoption.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the single-topic approach is not a fully broad and holistic one, from a regenerative perspective. Moreover, the rigour that may be hoped of such a standardised approach is not always present in practice (Giesekam et al, 2021). The SBTi permits annual emissions reductions of 2.5%, far less than what is appropriate to wealthy actors aiming for 1.5°C of global warming (Jackson, 2019;Masson-Delmotte et al, 2018).…”
Section: Programme Level: Standardised Modelsmentioning
confidence: 99%